2015
DOI: 10.1080/22243682.2015.1072732
|View full text |Cite
|
Sign up to set email alerts
|

Metallocene-containing polyesters from reaction of 3,5-pyridinedicarboxylic acid and metallocene dihalides and their preliminary ability to inhibit cancer cell growth

Abstract: Polyesters were rapidly formed employing the interfacial condensation of Group VB and vanadocene dihalides with 3,5-purinedicarboxylic acid. Infrared spectroscopy shows the formation of metalÀoxygen bonds. The products have a largely distorted non-bridging geometry about the metal atom. Matrix-assisted laser desorption/ionization mass spectrometry results are consistent with the formation of the polyesters. The polymers exhibit inhibition of the growth of pancreatic, colon, breast, and prostate cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…All band locations are given cm -1 . Infrared spectral analysis is consistent with the proposed structure and with other reported analyses for KA [14][15][16] and organotin polymers [17][18][19]. Table 2 contains results for the dibutyltin and diphenyltin polymers.…”
Section: Infrared Resultssupporting
confidence: 76%
“…All band locations are given cm -1 . Infrared spectral analysis is consistent with the proposed structure and with other reported analyses for KA [14][15][16] and organotin polymers [17][18][19]. Table 2 contains results for the dibutyltin and diphenyltin polymers.…”
Section: Infrared Resultssupporting
confidence: 76%
“…In the future we plan to employ this variability to design systems that allow a focus on Lewis bases that offer good ability to inhibit unwanted pathogens and infectious agents but where the polymer is not water soluble. We are at the initial juncture of this study [43].…”
Section: Water Soluble Polymersmentioning
confidence: 99%
“…These metal-containing polymers show good inhibition of a variety of human cancer cell lines [9,10,[36][37][38][39][40][41][42]. One focus is on pancreatic cancer since there is no good treatment once it has spread.…”
Section: Water-soluble Polymers Futurementioning
confidence: 99%
“…On the positive side, the absence of an effect on proliferative activity of the bone marrow, generally a dose-limiting side effect, was positive. Some phase II clinical trials were undertaken with patients with breast metastatic carcinoma [28] and advanced renal cell carcinoma [29]. Unfortunately, further clinical study was stopped because of the overall low activity observed.…”
Section: Treatment Of Cancermentioning
confidence: 99%
“…As in essentially all cases in our research, the reactants are commercially available, allowing for ready synthesis by others including in industry [13,[24][25][26][27][28][29]. The technique we employed is called the interfacial reaction or interfacial polycondensation process [1,2,[37][38][39].…”
Section: Treatment Of Cancermentioning
confidence: 99%